2016
DOI: 10.1161/circep.115.003333
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Atrial Fibrillation Beyond Short-Term Monitoring in Cryptogenic Stroke Patients

Abstract: Background— Atrial fibrillation (AF) can be a cause of previously diagnosed cryptogenic stroke. However, AF can be paroxysmal and asymptomatic, thereby making detection with routine ECG methods difficult. Oral anticoagulation is highly effective in reducing recurrent stroke in patients with AF, but its initiation is dependent on the detection of AF. Cryptogenic Stroke and Underlying Atrial Fibrillation (CRYSTAL AF) is the first randomized study to report the detection of AF in cryptogenic stroke pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(48 citation statements)
references
References 38 publications
2
43
1
2
Order By: Relevance
“…The randomized CRYSTAL AF study [19] demonstrated an AF detection rate of 12.4% within a monitoring period of 12 months. Thus, monitoring with an ICM leads to an eightfold higher detection rate of AF than using conventional methods [19,20]. The 18% AF detection rate in our study is in line with previous studies bearing in mind the longer monitoring period of 20 months.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The randomized CRYSTAL AF study [19] demonstrated an AF detection rate of 12.4% within a monitoring period of 12 months. Thus, monitoring with an ICM leads to an eightfold higher detection rate of AF than using conventional methods [19,20]. The 18% AF detection rate in our study is in line with previous studies bearing in mind the longer monitoring period of 20 months.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, numerous studies found increased detection rates of AF by ICM leading to ICM as the current standard of occult AF detection after cryptogenic stroke in many centres. The main advantage of ICM obviously is the long-term monitoring period, as in many cases AF is detected after a 30-day monitoring period [16][17][18][19][20]. Hindricks et al [16] reported a sensitivity of 96.1%, a specificity of 85.4%, a PPV of 79.3% and an NPV of 97.4% in detecting pAF.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of ischemic stroke on the risk of subsequent development of AF is only beginning to become clear [2, 3]. Information on development of new AF in ischemic stroke patients using ECG monitoring has been seldom reported until recently [46]. Clinical cardiovascular risk scoring tools such as the CHADS 2 and CHA 2 DS 2 -VASc have demonstrated association with development of first-ever AF during 2-year and 10-year follow-up time frames in recent studies [79].…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing research conducted by nurse scientists continues to play an influential role in helping individuals recognize, manage and alleviate their symptoms. One important issue related to AF is the difficulty of diagnosing and detecting AF, particularly when the patient is asymptomatic or may simply ignore symptoms such as fatigue and assume such symptoms are “normal” age related changes (Brachmann, et al, 2016). Additionally, symptoms of AF can mimic symptoms associated with other cardiac and non-cardiac underlying conditions (Hickey, et al, 2016).…”
Section: Symptom Self-management and Chronic Conditionsmentioning
confidence: 99%